2023
DOI: 10.1002/cncr.34717
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genomic profiling of circulating tumor DNA in pancreaticobiliary malignancies in plasma and bile

Abstract: Background: Obtaining sufficient pancreaticobiliary tumor tissue for genomic profiling has limitations. Liquid biopsies using plasma do not provide sufficient sensitivity. Thus, this study aimed to determine the effectiveness of liquid biopsy between bile and plasma for identifying oncogenic and drug-matched mutations.Methods: This study created a panel of 60 significantly mutated genes specific to pancreaticobiliary cancer (PBCA) and used it for genomic analysis of 212 deoxyribonucleic acid (DNA) samples (87 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Most of the studies reported above compare the performance obtained with paired tissue and bile samples, and all concur in that more genomic alterations could be detected in bile than in the corresponding tissue, in agreement with the fact that LB recapitulates tumor heterogeneity better than tissue biopsy [22,55,56,112]. In addition, the better sensitivity for cancer detection obtained in bile than in plasma is well demonstrated [21,22,55].…”
Section: Mutationssupporting
confidence: 63%
See 2 more Smart Citations
“…Most of the studies reported above compare the performance obtained with paired tissue and bile samples, and all concur in that more genomic alterations could be detected in bile than in the corresponding tissue, in agreement with the fact that LB recapitulates tumor heterogeneity better than tissue biopsy [22,55,56,112]. In addition, the better sensitivity for cancer detection obtained in bile than in plasma is well demonstrated [21,22,55].…”
Section: Mutationssupporting
confidence: 63%
“…Most of the studies reported above compare the performance obtained with paired tissue and bile samples, and all concur in that more genomic alterations could be detected in bile than in the corresponding tissue, in agreement with the fact that LB recapitulates tumor heterogeneity better than tissue biopsy [22,55,56,112]. In addition, the better sensitivity for cancer detection obtained in bile than in plasma is well demonstrated [21,22,55]. All in all, the increased sensitivity of new technologies, as well as the possibility to assess the presence of druggable-mutations, has boosted the potential utility of bile for both diagnosis of malignancy and targeting therapy.…”
Section: Mutationssupporting
confidence: 62%
See 1 more Smart Citation
“…Further work in this field will need to determine the etiology of the differences in oncogenic mutations between bile and plasma ctDNA and establish the clinical settings for when each will be most informative. The work from Ohyama et al 8 . is an important step in this progression.…”
Section: Cancer Type Fluid Methods Mutation Detection (%)A Matched Tumormentioning
confidence: 97%
“…In this issue of Cancer , Ohyama and colleagues 8 report a prospective study evaluating the performance of both plasma and bile cfDNA in 87 patients (59 cholangiocarcinoma [CC], 12 gallbladder cancer [GBC], and 16 PC). They found that bile had a higher sensitivity for the identification of oncogenic mutations than plasma (56% vs. 24%, respectively), and the variant allele frequency was overall higher in bile than plasma.…”
Section: Cancer Type Fluid Methods Mutation Detection (%)A Matched Tumormentioning
confidence: 99%